Perceptions of Teachers on Guidance and Counselling Services in Junior Secondary Schools in Moro Local Government of Kwara State, Nigeria - Kamaldeen, Rahmat Tinuke; Lasisi, Adekola Kamil (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2024)
The study explores the perceptions of Teachers on Guidance and Counselling Services in Junior Secondary Schools in Moro Local Government of Kwara State, Nigeria. The study used a descriptive survey design, which was mainly qualitative. The survey design is typically suitable when individuals aim to gather the opinions of participants to describe the characteristics of an existing phenomenon. The total participants of the study were 10 teachers. The primary method of data collection employed in this study was semi-structured interviews. The interviews utilised open-ended questions that aligned with the study's objectives and research questions. This study's findings indicate a common understanding among educators that guidance and counselling play a crucial role in fostering student development and ensuring school success. Concerns exist regarding the availability and effectiveness of these services. The findings suggest that schools should focus on enhancing the number of trained counsellors to provide sufficient support for students. This could entail governmental efforts to allocate resources for creating more positions and enhancing the ratios of counsellors to students.